Pengaruh Beban Kerja dan Kompensasi terhadap Turnover Intention dengan Employee Engagement sebagai Variabel Moderasi pada Karyawan Klinik Sabila Medika Group - Nasrullah, Nasrullah; Purwadhi, Purwadhi; Santoso, Budi (ProBisnis : Jurnal Manajemen, 2024)
Human resources (HR) have an important role in the sustainability of a company. Good HR management is needed in order to prevent, reduce, and overcome problems which often occur in companies, such as high turnover rates. Employee turnover is usually initiated by a group of symptoms of desire to leave the company, which is called turnover intention. Turnover intention is influenced by many factors, such as workload, compensation, and employee engagement. The purpose of this research is to find out the effect of workload and compensation on turnover intention with employee engagement as moderating variable. This research uses a quantitative approach with an explanatory method which tests the relationship between several variables through hypothesis testing. The sample used in this research was 40 subjects using questionnaire as a data collection instrument. The statistical instruments used are multiple linear regression analysis and moderated regression analysis with partial t test as hypothesis testing. The research results show that there is a significant positive effect of workload (<0.001) and a significant negative effect of compensation (<0.001) on turnover intention. The results also show that workload (0.000) and compensation (0.005) have a significant effect on turnover intention with employee engagement as a moderator.